Developmental absence of maxillary lateral incisors in the Portuguese population - Pinho, Teresa (2005)
The aim of this study was to evaluate the prevalence and clinical manifestation of developmental absence of maxillary permanent lateral incisors in the Portuguese population. The study group comprised 16 771 patients observed between 1993 and 2000 at the Faculty clinic. Two hundred and nineteen patients were found to have missing upper lateral incisors (131 females and 88 males, with ages ranging between 3 and 71 years), a prevalence of 1.3 per cent in this population. Absence of these teeth was bilateral in 44.7 per cent of the patients; of the unilateral cases, 33 per cent occurred on the right side and 21.9 per cent on the left side. In children under 8 years of age (n = 12), two (0.26 per cent) also had developmental absence of the primary lateral incisors, one unilateral and the other bilateral. Among the 121 subjects with unilateral developmental absence, the contralateral maxillary lateral incisor was found to be microdont in 57.1 per cent (right lateral 23 per cent, left lateral 34.1 per cent), suggesting the possibility that microdontia represents a variable expression of the same developmental defect that results in absence.